Faktor-Faktor Yang Mempengaruhi Income Smoothing Pada Perusahaan Manufaktur - Desi Sulistiawati, Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2021)
The purpose of this study is to empirically examine the influence of firm size, dividend payout ratio, cash holding and board size towards income smoothing in manufacturing companies listed in Indonesia Stock Exchange (IDX) from period 2016 – 2018. This study used 62 data from manufacturing companies that have been selected using purposive sampling method with total 186 data for thress years. The data used are secondary data in form of financial statements. This research used Eviews version 10.0 software to process the data. The result of research shows that board size have positive influence towards income smoothing. Firm size, dividend payout ratio and cash holding has no significant influence towards income smoothing.